2016
DOI: 10.1093/mmy/myw017
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of fungemia in an infectious diseases hospital in Mexico city: A 10-year retrospective review

Abstract: The epidemiology of invasive fungal infections has recently changed in immunosuppressed populations as a result of HIV infection, organ transplant, chemotherapy and in elderly patients. The diagnosis of invasive fungal infections by culture is prolonged since fungi grow slowly in vitro. we wanted to estimate the frequency of fungemia diagnoses established through the Clinical Mycology Laboratory over the past 10 years; through a retrospective study; data was obtained from the laboratory patient registry in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…A national survey conducted in Argentina identified cryptococcosis as the second most frequent deep fungal infection with a prevalence of 20%, following that of yeast fungemia ( Davel and Canteros 2007 ). In Mexico, C. neoformans had a prevalence of 21% causing fungemia in patients with different types of immunosuppression, only following Histoplasma capsulatum ( Gaona-Flores et al 2016 ). In the same country, cryptococcosis was the third most common invasive fungal infection (13%) found in a highly specialised hospital, following candidiasis and mucormycosis ( Méndez-Tovar et al.…”
mentioning
confidence: 99%
“…A national survey conducted in Argentina identified cryptococcosis as the second most frequent deep fungal infection with a prevalence of 20%, following that of yeast fungemia ( Davel and Canteros 2007 ). In Mexico, C. neoformans had a prevalence of 21% causing fungemia in patients with different types of immunosuppression, only following Histoplasma capsulatum ( Gaona-Flores et al 2016 ). In the same country, cryptococcosis was the third most common invasive fungal infection (13%) found in a highly specialised hospital, following candidiasis and mucormycosis ( Méndez-Tovar et al.…”
mentioning
confidence: 99%
“…In our study, histoplasmosis, aspergillosis, and pneumocystosis showed an increasing trend in the number of cases, possibly due to the fact that during the time in which this study was conducted, new methods were implemented for the detection of antigens and molecular diagnostic assays, methods that are characterized for having higher sensitivity values compared with conventional methods [14,15,[26][27][28][29][30]33,34,36]. In most studies, reports of patients with invasive candidiasis have been reported to be more frequent than what we found in our study [4,5,[10][11][12]. This may be explained by the fact that our laboratory is not affiliated with a hospital, where the majority of cases of invasive candidiasis arise.…”
Section: Discussionmentioning
confidence: 65%
“…Therefore, the findings regarding the frequency of IFD cannot be applied to the adult Colombian population. It is also important to note that, when comparing this research with other reported studies, many of them based in the diagnosis of IFD using conventional diagnostic methods, which do not provide very high sensitivity values, such as the immunodiagnostic and molecular methods used in this investigation [4,5,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluconazole-resistant C. albicans is the Candida yeast most frequently involved in diseases and is considered as a microorganism posing a serious hazard to humans, according to the Centers for Disease Control and Prevention (CDC) of the US Department of Health and Human Services [2]. A high incidence of candidiasis has been reported in hospitals, particularly in neonatal intensive care units, in HIV units and in organ transplant units [3][4][5].…”
Section: Introductionmentioning
confidence: 99%